2016
DOI: 10.1038/srep34274
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Amyloid Cores in Prion Domains

Abstract: Amyloids consist of repetitions of a specific polypeptide chain in a regular cross-β-sheet conformation. Amyloid propensity is largely determined by the protein sequence, the aggregation process being nucleated by specific and short segments. Prions are special amyloids that become self-perpetuating after aggregation. Prions are responsible for neuropathology in mammals, but they can also be functional, as in yeast prions. The conversion of these last proteins to the prion state is driven by prion forming doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 63 publications
(73 reference statements)
1
40
0
Order By: Relevance
“…The variation in amino acid sequence found to determine the propensity of amyloid formation 38,39 . In the present study, three consecutive novel polymorphic sites were identified in the first octapeptide repeat of the goat prion gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variation in amino acid sequence found to determine the propensity of amyloid formation 38,39 . In the present study, three consecutive novel polymorphic sites were identified in the first octapeptide repeat of the goat prion gene.…”
Section: Discussionmentioning
confidence: 99%
“…PHGGSRD (0.008) was predicted to have lower amyloidogenicity propensity than the wild type sequence PHGGGWG (0.096). As some proportion of amino acid sequence balance intrinsic amyloid formation and unwanted nucleation, these variants may create favourable conditions in the avoidance of non-physiologic folding 36,38 .Hotspot sequences with the H159 variant exhibited higher amyloidogenicity propensity than the wild type. The relatively higher destabilizing effect of H159 could be the potential reason why heptapeptides that included H159 had higher amyloidogenicity than other novel variants.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in yeast also allowed us to get a first glimpse on how physiological aggregation is regulated. We now know that functional aggregation generally depends on the presence of a prion-like, glutamine/ asparagine-rich domain, or a region of low compositional complexity (LCR), which interestingly are often found also in pathological aggregates [53,54]. Indeed, several proteins able to undergo reversible aggregation in yeast were shown to contain a predicted LCR, which likely triggers aggregate formation.…”
Section: Functional Amyloids: Towards An Understanding Of Their Regulmentioning
confidence: 99%
“…We wanted to test whether the soft amyloid cores predicted inside the PrLDs of these putative human prion-like proteins could spontaneously self-assemble into amyloid-like conformations and propagate their aggregated state, as we observed before for yeast prions 30 and the prion-like C. botulinum Rho factor 31 . We focused on nucleic acid-binding proteins, both because this molecular function is enriched in our dataset and because most of the experimentally validated yeast prions act in translational or transcriptional regulation.…”
Section: Resultsmentioning
confidence: 99%
“…This notion was implemented in pWALTZ, an algorithm that predicts the 21-residues long sequence stretch with the highest average amyloid potential in PrLDs 14 , 15 . This concept was further validated experimentally by demonstrating the existence of such soft amyloid stretches in the prion domains of four of the best characterized yeast prions 30 , as well as in the predicted PrLD of the Rho termination factor of Clostridium botulinum 31 , which later led to the discovery of the first bacterial prion-like protein 32 .…”
Section: Introductionmentioning
confidence: 88%